Reflection on Loving Pedagogy and Students' Engagement in EFL/ESL Classrooms - Zhao, Shengxue; Li, Manman (Frontiers in Psychology, 2021)
The role of positive emotions in language education has been exponentially approved in the literature. One such emotion which has been mostly neglected in EFL/ESL contexts due to irrational ethical and professional sensitivities is the concept of love. Although love in education highlights a caring environment and relationship which is oriented towards students’ feelings and needs, little (if any) research has been done on a loving pedagogy in the context of EFL/ESL. Trying to shed some light on this novel construct, this review article presents the theoretical underpinnings of love, its definitions, dimensions, and positive outcomes in language learning. Moreover, two trends of positive psychology and affective pedagogy are described. Finally, the study presents the possible implications of this line of research for different stakeholders in EFL/ESL domains along with a number of research gaps and future directions for avid scholars in this area.